PERBANDINGAN MUTU BERDASARKAN PROFIL DISOLUSI TABLET GLIBENKLAMID PATEN DAN GENERIK YANG BEREDAR DI MAKASSAR - Mursyid, A. Mumtihanah; Hasyim, Nursiah; Jauhari, Evy Fajrianti (Jurnal Ilmiah As-Syifaa, 2016)
A research of dissolution testing of patent and generic glibenclamide tablet have been done. The purpose of this research is to determine quality of patent and generic glibenclamide tablet that circulated in Makassar. Glibenclamide tablets patent and generic dissolution have been tested with paddle methode in 500 ml posfat buffer pH 7,4, medium was accomplished at 37 oCÂ±0,5 the speed of 75 rpm. Aliquot retaken as much 5 ml is done at time intervas of 10, 20, 30, 45, and 60 mnutes and then, the concentrations is confiruxed by spektrofotometer UV-VIS at the 299 nm wavelength. Based on the dissolution experiment result, the acquired glibenclamide percentage that was dissolute from glibenclamide tablets generic A = 85,686 %, generic B = 81,336 % and paten = 126,665 % have fulfill the dissolution the condition according to British Pharmacphea 2008. That is the dissolute is not less than 75 % within 45 minutes. And the average of Dissolution value efficiency (ED) rate each glibenclamide tablet paten = 115,29 %, generic B = 72,409 % and generic A = 77,352 %.